Adopsi Payment Gateaway Syariah: Peran Pengetahuan Riba Sebagai Moderasi - Beni Saputra; Alex Fahrur Riza (Journal of Business Management and Islamic Banking, 2023)
ABSTRACT Research Aims: This research aims to determine the adoption of Sharia Fintech services in the field of payment gateways using the UTAUT model with modifications to add knowledge of riba as a moderation variable. Design/methodology/approach: This research used an online survey method. The population this research are all users of Sharia payment gateway services. The sampling using the purposive sampling method with a total sample of 116 respondents. The analysis technique used is SEM-PLS using Smart PLS 3.3.3 software. Research Findings: The results of this research presented that Social Influence and Facilitating Condition have an effect in determining interest in using Sharia payment gateway services. Performance expectancy and effort expectancy have no effect on the interest in using Sharia payment gateway services. Meanwhile, in this research only in Effort Expectancy moderated by Knowledge About Riba.